Medical history screening for thrombophilic risk: is this adequate? - Eggert-Kruse, Waltraud; Ziegler, Andrea; Horlbeck, Sandra; Strowitzki, Thomas (Fertility and sterility, 2011)
Objective - To evaluate the reliability of medical history taken before hormonal medication administration to identify women with an increased risk for thromboembolic events detected by laboratory screening. - Design - Prospective study. - Setting - Outpatient endocrine clinic of a university-based hospital. - Patient(s) - Four hundred forty-three consecutive women (median age 49 years) who presented with endocrine disorders. - Intervention(s) - None. - Main Outcome Measure(s) - Parallel screening, on first visit, with a complete medical history, and same-day laboratory screening for thromboembolic risk. Laboratory examination in a two-step procedure with a standard assay and confirmation by genotyping on the second visit. - Result(s) - A total of 13.8% (61/443) patients with an abnormal activated protein C (APC) resistance test were identified. Second blood samples revealed a prevalence of factor V (Leiden) heterozygosity in 10.9% (homozygosity in 0.2%). There was a significantly higher prevalence of thrombotic events in a first degree relative of patients with APC resistance (in 18.3%) compared with women with a normal test outcome (in 7.8%). However, medical history (personal and family history) was negative concerning hints for thromboembolic events in more than 80% of patients with a laboratory risk profile for thromboembolic morbidity. No association of APC and factor V testing with the patients’ gynecological/obstetric history (e.g., live birth rate, miscarriages) was observed. - Conclusion(s) - Medical history alone may be inadequate to identify all patients at risk for thromboembolic complications with hormonal treatment.
Gesehen am 06.04.2022